Implementasi pendampingan suami terhadap istri yang mengalami kecemasan pada kehamilan trimester III di Klinik Barokah Medika Kemiling Bandar Lampung - Ikhwanudin, Ikhwanudin; Nurhayati, Nurhayati; Wijayanti, Novida Prima (Borobudur Nursing Review, 2025)
Pregnancy is a condition in which a woman has an embryo or fetus in her womb. Third trimester pregnancy is a pregnancy with an age of 28-40 weeks which is the time to prepare for birth and parenthood, and as a period of waiting. Anxiety is a vague and diffuse concern, which is related to feelings of uncertainty and helplessness. Husband assistance is a husband who accompanies or accompanies his wife in the labor process. This scientific paper aims to determine the characteristics of pregnant women who experience anxiety and determine the results of the implementation of husband assistance. The design of scientific papers is descriptive with a case study approach. The method used is the measurement of anxiety levels with HARS (Hamilton anxiety rating scale). The results of the implementation of husband assistance to mothers who experience anxiety are a decrease in the level of anxiety from the moderate to mild category. The conclusion of this scientific paper is that there is a decrease in anxiety, namely from the moderate category to the mild category.suggestion Pregnant women should know that the assistance of husbands, family and relatives is very important during the labor process because it can reduce anxiety.